FUNDAMENTALS OF SUPPLY - Mastilo, Zoran (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2014)
Product supply is the amount of products that a producer plans to sell within a given period of time. Volume of supply of a product depends on many factors, the most important being the price. In addition to that, there are other important factors about to be mentioned in this paper. The law of supply states that if the price of a product is at a higher level, the supply has also been increased with the assumption that the other factors that affect the supply have remained unchanged. The important aspect of supply is the production cost. If it remains unchanged, the higher price of the product shall bring higher profits to the producer. Therefore, higher profit represents an incentive for increasing the production volume. The supply curve displays the amount of supply with different product prices when other factors that affect the supply remain unchanged.